Strategies Proposed for Listening Comprehension in PBT TOEFL: Tricks that Do Not Work - Faisal Mustafa; Tomi Mandala Putra (Soegijapranata Catholic University, 2020)
Abstract: The Longman Preparation Course for the TOEFL, written by Phillips in 2003, is the most widely used coursebook for TOEFL test preparation. This book provides 17 strategies for Listening Comprehension Part A. Therefore, the current study examines whether the strategies provided in the book are applicable in a real test. The data were obtained from Part A of the TOEFL listening section in nine tests designed by Educational Testing Service (ETS). Each item in the test was tested against the proposed strategies. The results reveal that many items did not successfully match the strategies. Only two proposed strategies had matches of higher than 80%, while others were less than 10%. There are four strategies that did not have a match at all. All in all, very few strategies can be applied to answer the questions correctly without adequate comprehension. With comprehension, test takers can answer the questions without needing to rely on any of the proposed strategies. Therefore, the study concludes that most of the strategies proposed by Phillips (2003) are not successful in real test.Key words: strategies, PBT TOEFL, listening comprehension Abstrak: The Longman Preparation Course for the TOEFL yang ditulis oleh Phillips in 2003 paling banyak digunakan untuk pelatihan persiapan TOEFL. Buku tersebut berisi 17 strategi untuk menjawab soal TOEFP pada Part A. Oleh karena itu, penelitian ini menelaah apakah strategi dalam buku tersebut dapat digunakan untuk mengerjakan tes TOEFL yang sebenarnya. Data untuk penelitian ini diperoleh dari tes TOEFL bagian listening Part A yang diperoleh dari Educational Testing Service (ETS). Setiap soal pada tes tersebut dicocokkan dengan strategi yang terdapat dalam buku Phillips (2003). Hasil penelitian menunjukkan bahwa banyak soal tidak dapat dijawab dengan menggunakan strategi yang dianjurkan. Hanya ada dua strategi yang memiliki kecocokan lebih dari 80%, sedangkan yang lain kurang dari 10%. Ada dua strategi yang tidak cocok dengan satu soal manapun. Secara keseluruhan, sangat sedikit strategi yang dapat digunakan untuk menjawab soal TOEFL listening Part A tanpa pemahaman yang cukup. Dengan pemahaman, peserta tes bisa menjawab soal tanpa harus menggunakan strategi-strategi tersebut. Oleh karena itu, penelitian ini menyimpulkan bahwa kebanyakan strategi yang dikemukakan oleh Phillips (2003) tidak dapat digunakan untuk menjawab soal TOEFL asli.Kata kunci: strategi, PBT TOEFL, listening comprehension.